Sex, Drugs, and ADHD: The Effects of ADHD Pharmacological Treatment on Teens' Risky Behaviors - Anna Chorniy (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In the U.S., 8% of children are diagnosed with ADHD and 70% are taking medications, yet little evidence exists on the effects of ADHD treatment on children's outcomes. We use a panel of South Carolina Medicaid claims data to investigate the effects of ADHD drugs on the probability of risky sexual behavior outcomes (STDs and pregnancy), substance abuse disorders, and injuries. To overcome potential endogeneity, we instrument for treatment using physicians' preferences to prescribe medication. Our findings suggest that pharmacological treatment has substantial benefits. It reduces the probability of contracting an STD by 3.6 percentage points (7.7 percentage points if we include STD screening), reduces the probability of having a substance abuse disorder by 12.5 percentage points, reduces the probability of injuries by 3.1 percentage points per year, and associated with them Medicaid costs decrease by 122, or 0.07 standard deviation.
Keywords: I12; J18; I10; 330